2015
DOI: 10.14701/kjhbps.2015.19.3.109
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and safety of day-surgery laparoscopic cholecystectomy: a single-institution 5-year experience of 1140 cases

Abstract: Backgrounds/AimsWe report our experience with day-surgery laparoscopic cholecystectomy and assess its feasibility and safety.MethodsData was collected on all the patients who underwent day-surgery laparoscopic cholecystectomy between February 2009 and February 2014 at Prince Sultan Military Medical City, Riyadh, Kingdom of Saudi Arabia. All patients had symptomatic cholelithiasis that was proven on imaging studies with clearance of the common bile duct. The patient biographical data (age, gender, American Soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
0
6

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 7 publications
(10 reference statements)
3
8
0
6
Order By: Relevance
“…In the present study 16% of the patients scheduled for outpatient LC were not discharged after surgery as planned, which is comparable to the findings in other studies [1,7,10]. However, 21% of thesemainly staying in hospital due to excessive pain or PONV that could be controlled within a few hours -were discharged later on the same day.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…In the present study 16% of the patients scheduled for outpatient LC were not discharged after surgery as planned, which is comparable to the findings in other studies [1,7,10]. However, 21% of thesemainly staying in hospital due to excessive pain or PONV that could be controlled within a few hours -were discharged later on the same day.…”
Section: Discussionsupporting
confidence: 86%
“…The majority were treated conservatively with few episodes of major complications needing intervention such as laparoscopic re-surgery or stone extraction with ERCP. The results are comparable to those found in other studies [1,4,7,8,13]. Boehme et al [6] have looked into the relation between co-morbidity and postoperative resource utilization after LC and OC finding that certain comorbid conditions significantly increase utilization of postoperative resources including readmissions.…”
Section: Symptomatic Cholecystolithiasis 434supporting
confidence: 83%
See 1 more Smart Citation
“…Improvements in anaesthetics and increased surgeons laparoscopic experience have encouraged surgeons to perform LC as an elective outpatient procedure with only a few hours' hospital stay post-surgery. Many studies and literature reported the effectiveness and safety of ambulatory LC in selected patients, with reduced cost and high level of patient satisfaction [12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%
“…В последние годы в литературе встречаются публикации о выполнении лапароскопической хо-лецистэктомии (ЛХЭ) в условиях центров амбула-торной хирургии или стационаров одного дня [1][2][3][4][5].Основными преимуществами такого варианта лечения являются сокращение времени ожидания плановой операции, исключение риска развития го-спитальной инфекции, ускорение восстановления пациента за счет пребывания в домашних условиях, сокращение стоимости лечения, обследование, ле-чение и наблюдение за пациентом осуществляется одним врачом [6].Общее число послеоперационных осложнений (кровотечение, раневые осложнения) при выполне- Введение. в отечественной литературе сообщения о выполнении лапароскопической холецистэктомии (ЛХЭ) в амбула-торных условиях единичны.…”
unclassified